Fruit allergens and their allergenicity reduction: characteristics, technologies, and prospects - Tanying Zhang; Jinshen Chu; Yuntong Ying; Haochen Ye; Mengxian Li; Yiran Xie; Haozhe Yi; Jing Che; Bowen Li; Binjia Zhang; Xiaowen Pi (Trends in Food Science & Technology, 2026)

Integrated biochar-iron amendment mitigates rice cadmium uptake via soil immobilization, iron plaque barriers, and microbial community restructuring - Meiling Xu; Tianyi Hu; Fangge Xu; Jing Che; Guobing Wang; Yepu Li; Qiao Xu; Xiaozhi Wang (Journal of Environmental Chemical Engineering, 2026)

Synergistic effects of lipid degradation and the Maillard reaction: Decoding the flavor formation of charcoal-grilled lamb skewers based on flavoromics, sensomics, metabolomics, and lipidomics - Che Shen; Xinyu Jiang; Jiajin Sun; Meiyi Li; Ran Wang; Yunhui Zhang; Jing Tian; Lizhang Wu; Xiongfeng He; Bo Wang; Kezhou Cai; Baocai Xu (Food Research International, 2026)

Ventilation and air conditioning design for interconnected large-space underground pumped storage power stations and prediction method for spatial temperature distribution - Lianhua Deng; Jigang Che; Angui Li; Shaofeng Niu; Jing Xiong; Ying Zhang (Building and Environment, 2026)

A physics-informed neural network for continuous rice canopy thermal monitoring and forecasting from sparse UAV observations - Peng Xie; Yuan Wang; Changwen Du; Jing Che; Haitao Xiang (Computers and Electronics in Agriculture, 2026)

Sulfated dialogues: How brown algae polysaccharides orchestrate gut-host crosstalk through structure-encoded signals - Jing Xu; Yanjing Liu; Sitong Che; Mengqian Ma; Wanyu Tang; Peng Zhang; Yuanqiang Guo (Trends in Food Science & Technology, 2026)

A comparative structural and proteomic analysis of bovine milk fat globule membrane (MFGM) ingredients: Industrial vs laboratory isolation approaches - Jing Che; Wanxiang Guo; Manja Mahmens Fabricius Møbjerg; Søren Drud-Heydary Nielsen; Nina Aagaard Poulsen; Lotte Bach Larsen (Food Chemistry, 2026)

Efficient vitrification of hazardous waste incineration fly ash and slag via the CaO-SiO2-Fe2O3 system - Yuyang Long; Zheyu Chen; Yuhe Song; Chen Liu; Jing Hou; Lei Che; Wangyang Tian; Weiwei Zhao; Bochao Dong; Dongsheng Shen; Foquan Gu (Environmental Research, 2026)

Robust ultralong multicolor phosphorescence with high-temperature resistance and dynamic stimulus-responsive color-changing afterglow enabled by in situ synergetic rigidification - Wenjing Chen; Jiqiu Yang; Yi Zhu; Pengfei Du; Shujuan Liu; Jinxiu Che; Yinna Zhang; Jing Yang; Baozhong Lü; Feng Peng; Zhengjun Shi (Chemical Engineering Journal, 2026)

Retraction notice to “Cable-car measurements of vertical aerosol profiles impacted by mountain-valley breezes in Lushan Mountain, East China” [Sci. Total Environ. 768 (2021) 144198] - Jing Duan; Yong Chen; Wenling Wang; Jun Li; Xiaopeng Zhang; Guangxian Lu; Yunfei Che; Shujun Zhong; Shupo Ma; Peng Li; Junling An; Pingqing Fu (Science of The Total Environment, 2026)

Activation-optimized anti-CD3 valency control enables combinatorial discovery of multi-specific nanoantibodies for solid tumor immunotherapy - Long Zhu; Ya-Jing Ma; Jian-Kang Kang; Xiu-Hai Che; Dong-Kun Zhao; Yin-Yi Cai; Yao-Ru Yu; Song Shen; Jun Wang (Science Bulletin, 2026)

MXene-enhanced self-healing nanocomposite hydrogels with multiple-dynamic-bond crosslinking for motion sensing and information transmission - Ze-Hua Hou; Huan-Jie Che; Zi-Han Jiang; Xing Wu; Jin-Ping Yuan; Jing Li; Jian-Bo Qu (Chemical Engineering Journal, 2026)

Research progress on the characteristics of milk allergens and the effect of Maillard reaction and its assistance treatment on allergenicity - Xiaowen Pi; Tanying Zhang; Jia Cao; Zeyu Peng; Bowen Li; Haozhe Yi; Wanxiang Guo; Jing Che; Chen Wang; Jinshen Chu (Food Chemistry, 2026)

Scale up fermentation of Chenopodium formosanum dairy products with process optimization and evaluation of ACE inhibitory peptides and antioxidant activity - Chen-Che Hsieh; Jing-Rong Wu; Yi-Cheng Huang; Shin-Ping Lin; Jheng-Jhe Lu; Adyasa Barik; Shella Permatasari Santoso; Chang-Wei Hsieh; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2026)

Biosynthesis, extraction, identification, biological activities, and biomedical applications of cephalopod ink melanin - Chunsen Xia; Baolian Jing; Jiaxin Duan; Miaomiao Zhou; Xiaoran Li; Hongyan Li; Hongxia Che (Food Bioscience, 2026)

Spatiotemporal evolution and ecological risk assessment of heavy metals in agricultural black soils of Northeast China - Tianhao Che; Boling Deng; Naiwen Hu; Meixuan Wu; Hongwen Yu; Jing Yue; Quanying Wang (Environmental Research, 2026)

A secreted alpha-amylase effectively induces reproductive cyst formation both within and across Colpoda species, key soil-dwelling protists - Zixin Cheng; Zhongqiao Song; Kejia Fu; Yuan Wang; Kai Chen; Jing Zhang; Che Hu; Xiaocui Chai; Shuai Luo; Fang Zhou; Yuan Xiao; Zhenfei Xing; et al. (Science China Life Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel artificial air life support system based on liquid oxygen and liquid nitrogen in underground refuge chamber - Haolin Lu; Angui Li; Jigang Che; Yuanqing Ma; Lianhua Deng; Jing Xiong; Changqing Yang; Dingmeng Wu (Energy and Buildings, 2026)

From nature to clinic: Lessons from successfully marketed polysaccharide drugs - Jing Xu; Wanyu Tang; Sitong Che; Jia Wang; Ke Liu; Jiaxin Duan; Yuanqiang Guo (Carbohydrate Polymers, 2026)

Regulatory patterns and driving factors of soil aggregates on the environmental behavior of heavy metals: A global study based on meta-analysis and machine learning - Yu-Xuan Song; Yuhan Meng; Bingxuan Zhao; Tian-Hao Che; Zining Li; Zuozhou Yu; Xinyang Zhen; Yining Li; Chengyong Li; Quan-Ying Wang; Jing-Ya Zhou (Environmental Geochemistry and Health, 2026)

Tetrabromobisphenol A and Cadmium Chloride Induced Hepatic Oxidative Stress and Autophagy Inhibition in Rats - Rongjing Sun; Jing Tian; Li Che; Tianyang Liu; Huibin Jin; Haonan Zhao; Jin Chen; Nianping Zhang; Xi Kang; Luqing Pan; Piaoye Wu; Bei Liu; et al. (Biological Trace Element Research, 2026)

Long Hypocotyl 1 mediates nitrogen regulation of flowering time and nitrogen use efficiency - Xingliang Duan; Guanjie Wang; Qinglin Song; Jiale Liu; Huilin Ding; Jing Che; Wei Xuan (Plant Science, 2026)

Physics-informed βVAE-transformer reduced order surrogate model for fast and accurate prediction of offshore natural gas leakage concentration fields - Houjia Xu; Bingcai Sun; Qi Jing; Qianfan Che; Yuntao Li; Yang Cao; Junyao Wu (Ocean Engineering, 2026)

Application of biochar-based permeable reactive barriers in environmental remediation: A critical review - Chang Liu; Ruijie Che; Zhongtian Dong; Jing Hua; Ning Xu; Yining Zhu; Fenghe Wang; Shengtian Zhang (Journal of Environmental Management, 2026)

China's underestimated, characteristic herpetofauna pet trade highlights the importance of global efforts in conservation - Kai Wang; Chenqi Lu; Shuo Qi; Pipeng Li; Robert W. Murphy; Cameron D. Siler; Jing Che (Biological Conservation, 2026)

Strategic directions for mitigating cultivated soil acidification in China: Insights from global progress and local practice - Ren Fang SHEN; Ying TENG; Jing CHE; Xueqiang ZHAO (Pedosphere, 2026)

Valorization of fly ash into hydrophobic mesoporous SiO₂ as a highly efficient and durable antifoaming agent for wet flue gas desulfurization - Fei Wang; Xiaoyan Yan; Xiaoke Li; Jiangtao Meng; Yu Che; Jing Wang; Yuanyuan Zhang (Journal of Environmental Chemical Engineering, 2026)

Unlocking the potential of functional food polysaccharides: The zebrafish model as a revolutionary high-throughput screening platform - Yanjing Liu; Sitong Che; Jing Xu; Yuanqiang Guo (Carbohydrate Polymers, 2026)

Structure characterization, antioxidant and β-cell protective effects of the glutaredoxin 2/glutathione system and glutathione metabolism-related Lonicerae Japonicae Caulis pectin - Xiaodan Qi; Hao Cheng; Huixin Sui; Youxian Kang; Jingyi Yang; Yuwen Wang; Xianbin Liu; Baoping Xu; Limei Che; Jing Xu; Chunjing Zhang (Carbohydrate Polymers, 2026)

Effects of water table depth and fluctuations on Sphagnum palustre growth and plant community succession in subtropical mountainous Sphagnum peatlands: insights from a microcosm experiment - Ting-Ting Li; Man-Jing Tian; Jie Xu; Lun-Che Wang; Bin-Luo Li; Hui-Hui Sun; Wen-Yi Yang; Zheng-Xiang Wang (Aquatic Sciences, 2026)

Mechanisms of water-state transformations in low-temperature thermal dewatering of sludge: Synergistic control via extracellular protein α-helix conformation and water–solid interfacial affinity - Nan Tian; Yu Hua; Fei Wang; Kai Zhang; Yuanyuan Zhang; Jing Wang; Yu Che; Jiangtao Meng; Fangqin Cheng (Bioresource Technology, 2026)

LSTM-CNN-CBAM-based prediction of NOx emissions with zonal control strategies for flexible peak-load NOx reduction in CFB coal-fired units - Jing Wang; Xinwen Liao; Yu Che; Pengcheng Wang; Yuanyuan Zhang; Fei Wang; Frédéric Marias; Haojie Rong (Journal of Cleaner Production, 2026)

Sepia pharaonis ink derived melanin ameliorated high-fat diet induced lipid dysmetabolism: Insights from microbiome and hepatic transcription - Miaomiao Zhou; Chunsen Xia; Baolian Jing; Jiaxin Duan; Hongyan Li; Hongxia Che (Food Research International, 2026)

Phthalate ester pollution poses a potential threat to soil organisms: Insights from a global meta and machine-learning analysis - Haiyi Zhang; Tianhao Che; Hongwen Yu; Jing Yue; Quanying Wang (Environmental Research, 2026)

Mechanosensor YAP orchestrates human neural rosette morphogenesis via TEAD4-LEF1 transcriptional nexus - Jinghao Hu; Zan He; Huifang Hu; Xiaoyan Sun; Shanshan Che; Shuhui Sun; Miyang Ma; Yixin Zhang; Shuai Ma; Weiqi Zhang; Juan Carlos Izpisua Belmonte; Guoguang Zhao; et al. (Science China Life Sciences, 2026)

An electrochemical-photothermal platform driven by DNAzyme walker and HCR on MoS2@ZIF-67 heterojunction substrate for ultrasensitive phytopathogen detection - Bingtao Fu; Yunzhi Ma; Rongshuai Che; Haibo Wang; Yanni Luo; Defen Feng; Ke-Jing Huang; Shengyu Xie (Analytica Chimica Acta, 2026)

Vegetation cover affects the response of greenhouse gas emissions to microplastics in a coastal wetland - Feifei Yan; Zihao Wang; Caijie Zhang; Ling Zhang; Zhikai Wang; Chunguang Che; Yuchi Xia; Jing Zhang (Water Research, 2026)

(E)-2-((E)-oct-2-en-1-ylidene)-hydrazine-1-carbothioamide inhibited the growth of Penicillium italicum by disrupting mitochondrial energy metabolism - Yafeng Li; Yonghua Zhang; Liangliang Gao; Jing Liu; Qiuli Ouyang; Jinxin Che; Nengguo Tao (Postharvest Biology and Technology, 2026)

CYP51B is involved in the prochloraz resistance of two newly isolated Penicillium italicum strains from citrus fruit - Tengjie Li; Yun Zhou; Jing Liu; Yue Chen; Jinxin Che; Nengguo Tao (Postharvest Biology and Technology, 2026)

Lanthanum strengthens Solanum nigrum remediation of arsenic-contaminated soils: From detoxification mechanisms to risk reduction - Yining Zhu; Ruijie Che; Jing Hua; Chang Liu; Zhongtian Dong; Ning Xu; Mingzhu Xia; Fenghe Wang (Journal of Hazardous Materials, 2026)

Hybrid nanozyme-natural enzyme catalytic system-based self-powered biosensing platform with dual-signal output for trace-level monitoring of pathogens - Bingtao Fu; Rongshuai Che; Haibo Wang; Yanni Luo; Defen Feng; Jiawen Wu; Jun Yan; Ke-Jing Huang; Xuecai Tan (Chemical Engineering Journal, 2026)

Evaluation of salt tolerance in Agropyron Gaertn.: key indicators, optimal conditions, and implications for crop improvement - Jiarui Zou; Jing Yang; Ying Liu; Yanping Yang; Lai Wei; Haiming Han; Shenghui Zhou; Weihua Liu; Jinpeng Zhang; Lihui Li; Yonghe Che (Genetic Resources and Crop Evolution, 2026)

Volatilomic profiling of controlled atmosphere stored blue honeysuckle fruit using GC-MS, E-nose, and GC-IMS - Zhen Xiao; Qiuju Jing; Shuangyu Xie; Jinhui Sun; Jianing Che; Junwei Huo; Xiaonan Sui; Yaqi Lan; Yan Zhang (Postharvest Biology and Technology, 2025)

Enhanced retention of microplastics in biopolymer-modified porous media: Insights from pore-scale visualization - Zi Wang; Jin Liu; Gang Zhang; Meng Wu; Yuhan Feng; Yue Yang; Wenyue Che; Miao Jing (Journal of Hazardous Materials, 2025)

Combined toxicity of microplastics and heavy metals to terrestrial plants: A global meta-analysis integrating machine learning predictions - Ye-Qian Zhen; Tian-Hao Che; Yu-Xuan Song; Ya-Ming Wan; Hai-Han Jiang; Zuo-Zhou Yu; Miao Yu; Shi-Qi Xu; Cheng-Yong Li; Jing-Ya Zhou (Journal of Environmental Chemical Engineering, 2025)

Enhanced cobalt removal through coupled ultrasonic and oxygen potential regulation: A novel process study - XiaoQian Che; Jing Chen; WanTao Ning; Libo Zhang; ChuanYu Li; Jing Li; BaoXin Liu; JunChang Liu (Journal of Environmental Chemical Engineering, 2025)

Nontargeted metabolomics combining with intestinal microbiota revealed the potential mechanisms of DHA/EPA - acetylated astaxanthin esters in regulating the abnormal lipid metabolism - Xiaoran Li; Baolian Jing; Chunsen Xia; Xiyu Wang; Xing Qiao; Tiantian Zhang; Hongyan Li; Hongxia Che (Food Research International, 2025)

Development of risk-based critical limits in HACCP plans through quantitative microbial risk assessment: Salmonella risk in a poultry meat supply chain case in Taiwan - Che-Lun Mai; Yu-Hao Chou; Kelvin Chou; Fang-Jing Song; Hsin-I Hsiao (Food Control, 2025)

Machine learning-enhanced meta-analysis unravels the global patterns of microplastic-heavy metal co-toxicity in terrestrial ecosystems - Hai-han Jiang; Tian-Hao Che; Qing Su; Bin Jin; Yan Lu; Han-Xi Zhou; Min-Jie Fu; Jing-Ya Zhou (Environmental Pollution, 2025)

Optimizing nitrogen form ratio for enhanced nutrient uptake and lettuce performance in hydroponic systems - Jing Xu; Gongye Che; Junqi Yan; Yun Luo; Allen Good; Tian Yuan; Zhongfang Lei; Zhenya Zhang; Kazuya Shizumi (Bioresource Technology Reports, 2025)

Cell-supporting cytoskeletons and phagocytic acquisition of compatible solutes emerge as common strategies for high-salt adaptation in different ciliates - Fengchao Li; Wenying Zhang; Shuai Luo; Ning Ma; Jing Zhang; Weiwei Qin; Che Hu; Xinxin Gao; Yuan Xiao; Chuanqi Jiang; Xiaocui Chai; Qiukun Wang; et al. (Science China Life Sciences, 2025)

High Quality, Granular, Timely, Trustworthy and Efficient Vertebrate Species Distribution Data Across a 30,000 km 2 Protected Area Complex - Yinqiu Ji; Alex Diana; Xueyou Li; Eleni Matechou; Jim E. Griffin; Shuwei Liu; Mingjie Luo; Chunying Wu; Ru Bai; Chenyang Yao; Tingting Yin; Feng Dong; et al. (Ecology Letters, 2025)
The routine generation of species distribution data at scale remains a challenge. We used aquatic environmental DNA metabarcoding to sample vertebrate species across the 30,000 km 2 Gaoligongshan region along the China–Myanmar border. In just 56 calendar days (33 researcher‐field‐days + 69 researcher‐lab‐days), we detected 389 vertebrate species, of which 35 are Red‐Listed. We introduce the ‘eDNA‐aware’ OccPlus occupancy model, which accounts for false‐negative and false‐positive error in the field and lab. OccPlus leverages the taxonomic breadth of eDNA datasets by using ordination to estimate species occupancies. We recover known biogeographic patterns and find that native terrestrial and fish species have higher occupancies inside protected areas while domesticated species and non‐native fishes have higher occupancies outside them. Our study demonstrates how eDNA metabarcoding can obtain high‐quality, granular, timely, trustworthy and efficient species distribution data to facilitate nature conservation and restoration.

Investigation of the impact of local tumor phenolic-chemistry for dual starvation and vaccination therapy - Jingsong Lu; Zhenhu Guo; Sumei Chen; Ying Li; Xin Xu; Jing Yu; Shenglei Che; Guifeng Zhang; Wensheng Xie; Yen Wei; Lingyun Zhao (Chemical Engineering Journal, 2025)

Mapping snow cover frequency at 30 m for studying seasonal variations and topographic controls on the Tibetan Plateau - Guigang Wang; Tao Che; Liyun Dai; Yanxing Hu; Jun Wu; Saiyao Meng; Chuilei Kong; Jing Wang; Dongdong Feng; Shijie Wang; Xuemei Li (Journal of Hydrology, 2025)

Influence of biopolymer-based topsoil treatments on surface-subsurface hydrological processes: Implications for protection and restoration of sandy slopes - Jin Liu; Runqi Zhang; Miao Jing; Simin Yang; Zezhuo Song; Wenyue Che (CATENA, 2025)

Variation of flavor substance-producing microbiota in four seasons of Chinese liquor fermentation - Feng Liang; Zhiming Zhong; Shibo Ban; Ping Ma; Jing Hao; Jing Wu; Heqiang Huang; Fuhong Che; Qun Wu; Yan Xu (Systems Microbiology and Biomanufacturing, 2025)

Assessment of Egg Yolk IgY Antibodies Against Live or Inactivated Aeromonas hydrophila for Polyvalent Passive Immunization in Goldfish (Carassius auratus) - Pan Cui; Jing Chen; Huihui Xiao; Xixian Che; Shujun Sun; Zijian Ma; Juan Lu; Gaoxiao Xu; Xiang Liu (Fishes, 2025)
Egg yolk IgY antibody has significant application potential in aquaculture as a form of passive immunotherapy against various bacterial infections owing to its capacity for large-scale and cost-effective production. In this research, laying hens were immunized with live or inactivated Aeromonas hydrophila to produce IgY antibodies. Following this, experiments were carried out to assess the passive immune protection rates of the two types of IgY antibodies when used to immunize goldfish (Carassius auratus), which were then infected with A. hydrophila or Aeromonas veronii. ELISA experiments were conducted to demonstrate the interaction between the IgY antibodies and the bacteria. The kidneys of C. auratus were coated on a Luria–Bertani (LB) medium to evaluate bacterial content. The leukocyte phagocytosis was detected by a cell phagocytosis assay. The serum of C. auratus was used to assess the expression of antioxidant factors, and a qRT-PCR was conducted to evaluate the mRNA expression of inflammatory factors in visceral tissue. Furthermore, histopathology and immunofluorescence analysis were performed to evaluate the structural integrity, apoptosis, and DNA damage of visceral tissues. The results indicated that the live or inactivated A. hydrophila IgY antibodies exhibited passive immune protection rates against A. hydrophila and A. veronii and could recognize these two bacteria in vitro. Additionally, these two IgY improved the phagocytic ability of leukocytes, diminished renal bacterial concentration, and decreased the levels of antioxidant factors and mRNA expression of inflammatory factors. Meanwhile, the two IgY antibodies did not cause any pathology of the kidney, spleen, and intestine, and decreased the levels of DNA damage factor (γH2A.X) and cell apoptosis factor (p53) in renal tissue. Therefore, live and inactivated A. hydrophila IgY antibodies can resist bacterial infections, with live bacteria IgY providing greater protection than inactivated bacteria IgY. Further, A. hydrophila is an aquatic pathogen that causes minimal damage to laying hens, and the immunity of live A. hydrophila conforms to animal welfare. Altogether, live A. hydrophila IgY antibody can serve as a polyvalent passive immune vaccine candidate in aquaculture.

Estimating carbon fluxes over North America using a physics-constrained deep learning model - Bin Fan; Hankui K. Zhang; Zhongbin B. Li; Jingfeng Xiao; Xianghong Che; Zhihua Liu; Gustau Camps-Valls; Jing M. Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Transcriptome analysis of wheat identifies key genes involved in iron and zinc distribution and signaling - Ting Qu; Ren Fang Shen; Jing Che (Plant and Soil, 2025)

Shifts in Bacterial Community Structure and Phosphorus-solubilizing Bacteria Abundance in Rhizosphere of Tibetan Barley along a Gradient of Soil Phosphorus Availability - Jing Che; Hao Zhou; Heng Zheng; Tongxin Zhao; Xing Liu (Journal of Soil Science and Plant Nutrition, 2025)
As the phosphorus (P) availability limits nutrient uptake and yield of crop plants, there is an urgent need to explore more P-solubilizing microorganisms and the influencing factors of their abundance in the field. However, it remains unclear how environmental and plant-related factors affect both total bacterial community and P-solubilizing bacteria in various P regime. In this study, we characterized the rhizosphere bacterial communities of Tibetan barley at 29 sites (classified into four soil types with varying AP contents) in a field survey as well as different barley origins in a field control experiment (located in Lasa and Linzhi) in China. We identified the P-solubilizing capacity of isolated bacterial strains in vitro and explored their distribution and relative abundance in the bacterial communities of Tibetan barley plants across sites and soil types. Our results found that Bacillus and Pseudomonas bacteria with the P-solubilizing capacity could be widely distributed in the rhizosphere of barley plants at different sites. Relative abundance of P-solubilizing bacteria and bacterial community structure, including the relative abundance of both dominant phyla and genera, OTUs richness, and Shannon index, varied greatly among the four soil types and was also related with soil available P content. These parameters were only affected by experimental location rather than plant seed origin, mainly due to a stronger influence of soil conditions in shaping root-associated bacterial community compared to plant-related factors. Overall, our study highlights the necessity of combining field survey and experimental approaches to explore the underlying mechanisms of plant-soil microorganism interactions.

Differential catalytic mechanism induced by selective adsorption of pollutants in metal clusters decorated single atom catalyst mediated heterogeneous Fenton-like reaction - Hanxuan Zeng; Yibo Che; Bufan Yang; Jing Deng; Changyong Zhang; Jue Wang; Haojie Zhang (Journal of Hazardous Materials, 2025)

Improvement of flavor and inhibition of accompanying harmful substances in roasted fish by different tea pre-marinades - Cheng-Zhen Nie; Jing Che; Ji Wang; Xu-Hui Huang; Lei Qin (Food Chemistry, 2025)

Enzymatic dephosphorylation of isolated bovine caseins: Targeted modulation of phosphorylation degree via pH and reaction time optimization - Jing Che; Wanxiang Guo; Nina Aagaard Poulsen; Lotte Bach Larsen (Food Bioscience, 2025)

Polyvalent immunoprotection of protein, DNA and IgY antibody vaccines of Vibrio fluvialis outer membrane protein VF08100 in fish - Huihui Xiao; Saixing Duan; Pan Cui; Jing Chen; Xixian Che; Juan Lu; Juan Wang; Guoping Zhu; Yong Liu; Xiang Liu (Fish & Shellfish Immunology, 2025)

Investigating the impact of fecal contamination on antibiotic resistance genes in urban environments using host-associated molecular indicators - Yujing Duan; Hui She; Lingna Jing; Lianrui Duan; Jinxiu Zheng; Ying Shao; Yuxin Che; Yu Shi; Chao Guo; Wenhui Zhao; Tao Yang; Lijun Yang (Environmental Pollution, 2025)

The Supplementary Motor Area as a Flexible Hub Mediating Behavioral and Neuroplastic Changes in Motor Sequence Learning: A TMS and TMS-EEG Study - Jing Chen; Yanzi Fan; Xize Jia; Fengmei Fan; Jinhui Wang; Qihong Zou; Bing Chen; Xianwei Che; Yating Lv (Neuroscience Bulletin, 2025)

Development and evaluation of an electrical impedance tomography (EIT) sensor for real-time monitoring of hemolysis dynamics - Piao Peng; Yue Fu; Bo Che; Xuan Li; Lei Liu; Jing Sun; Teng Luo; Linhong Deng (Analytica Chimica Acta, 2025)

Rent-seeking behavior of ship sulfur emission detection based on evolutionary game theory - Jing Liang; Liang Dong; Yuhang Che; Yu Tang; Yuying Dou (Regional Studies in Marine Science, 2025)

Phase transformation of calcium sulfate at mineral-solution interface: An overlooked pathway for selective enrichment of cadmium - Wenjing Li; Guiquan Che; Chunli Wang; Zhihao Zhang; Jing Zhang; Zhang Lin (Journal of Hazardous Materials, 2025)

Low-frequency rTMS Plays a Neuroprotective role in Pilocarpine-induced Status Epilepticus Rat Models Through the AMPAR GluA1–STIM–Ca2+ Pathway - Li-Qin Che; Zhen-Zhen Qu; Zhuo-Feng Mao; Qi Qiao; Kai-Ping Zhou; Li-Jing Jia; Wei-Ping Wang (Molecular Neurobiology, 2025)

Cellular milk production: Proteins and minerals in secretomes from cultivated bovine milk-derived mammary cells - Jing Che; Yuan Yue; Gayani M.S. Lokuge; Søren Drud-Heydary Nielsen; Ulrik Kræmer Sundekilde; Stig Purup; Lotte Bach Larsen; Nina Aagaard Poulsen (Food Chemistry, 2025)

Molecular characterization of TRAF gene family in snakehead (Channa argus) - Xiu Feng Han; Ming Yue Che; Xue Su; Jing Yun Tian; Lan Hao Liu; Pin Nie; Su Wang (Fish & Shellfish Immunology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Associations between co-exposure to multiple heavy metals and age-related macular degeneration: A cross-sectional study - Mu-hong Wei; Ju-xiao Li; Jing Mi; Qing Wang; Feng Xu; Che Xu (Journal of Trace Elements in Medicine and Biology, 2025)

Uncovering the impacts of social comparative information on water saving behavior among urban residents: A field experiment in China - Juan Wang; Le Wen; Yongbo Li; Jing Liu; Shuai Che (Journal of Cleaner Production, 2025)

Mechanical deformation destabilizing hydrate within thermodynamic equilibrium region - Peng Zhang; Xueping Chen; Rui Bao; Xu Ma; Yulu Wang; Yangli Che; Lianhai Zhang; Yingmei Wang; Jing Zhan; Guangjun Guo; Changyu Sun; Jianyang Wu; et al. (Fuel, 2025)

Unravelling the dominant role of phosphorylation degree in governing the functionality of reassembled casein micelles: Implications for future dairy production through precision fermentation - Jing Che; Zekun Fan; Etske Bijl; Julia Prangchat Stub Thomsen; Ivan Mijakovic; Kasper Hettinga; Nina Aagaard Poulsen; Lotte Bach Larsen (Food Hydrocolloids, 2025)

Tandem synergetic effect in symbiotic Co catalyst for enhanced oxygen reduction - Jing Zhang; Meihuan Liu; Yuhao Zhang; Hui Su; Xiuxiu Zhang; Baojie Li; Jianglong Guo; Youcai Che; Weiren Cheng; Qinghua Liu (Chemical Engineering Journal, 2025)

Deferoxamine functionalized alginate-based collagen composite material enhances the integration of metal implant and bone interface - Zhenjia Che; Xiao Sheng; Qi Sun; Yanglin Wu; Kaihang Song; Aopan Chen; Jing Chen; Qiyun Chen; Ming Cai (Carbohydrate Polymers, 2025)

Assessing the interaction of oceanic and riverine processes on coastal phytoplankton dynamics in the East China Sea - Jiawei Gao; Rong Bi; Julian P. Sachs; Yaoyao Wang; Yang Ding; Hong Che; Jing Zhang; Peng Yao; Jie Shi; Meixun Zhao (Marine Life Science & Technology, 2025)
The interaction of riverine inputs and ocean current systems causes complex spatiotemporal variations in phytoplankton dynamics in marginal seas of the northwest Pacific Ocean, yet quantitative assessments of these variations and their causes remain limited. Here we evaluate phytoplankton biomass and community structure changes using lipid biomarkers, accompanying ocean circulation and nutrient variations in surface waters collected in spring and summer of 2017–2018 at 118 sites in the East China Sea off the Zhejiang coast. High biomass of diatoms, inferred from brassicasterol concentrations, shifted from the south in spring to the north in summer, while high dinoflagellate biomass, inferred from dinosterol concentrations, occurred mainly in the Changjiang (Yangtze) River plume and adjacent areas in both seasons. Seasonal variation in phytoplankton distribution was linked to the spatial extents of water masses such as the Changjiang Diluted Water (CDW) and the intrusion of the Kuroshio Subsurface Water (KSSW). A three end-member mixing model was applied to quantify water mass contributions. The results showed that an increase in the KSSW (from 0 to 40%) and a decrease in the CDW (from 100 to 20%) resulted in a significant (20%) increase in diatom proportions and a significant (20%) decrease in dinoflagellate proportions. Dinoflagellate proportions were highest in the CDW-dominated region, while diatoms and total phytoplankton biomass were higher in the CDW–KSSW mixing region and the KSSW-dominated region. This study highlights the dynamic response of the phytoplankton community to water mass changes in marginal seas that can aid coastal ecosystem management.

A comprehensive molecular phylogeny of the genus Sylvirana (Anura: Ranidae) highlights unrecognized diversity, revised classification and historical biogeography - Yun-He Wu; Man-Hao Xu; Chatmongkon Suwannapoom; Sang Ngoc Nguyen; Robert W. Murphy; Theodore J. Papenfuss; Amy Lathrop; Felista Kasyoka Kilunda; Wei Gao; Zhi-Yong Yuan; Jin-Min Chen; Liang Zhang; et al. (Molecular Phylogenetics and Evolution, 2025)

Copper/iron bimetal phenolic networks boosted apoptosis/ferroptosis/cuproptosis combined tumor therapy through dual glutathione depletion - Fan Zhao; Hongyan Yu; Chen Wang; Junchen Xu; Hao Gao; Yao Ying; Wangchang Li; Juan Li; Jingwu Zheng; Liang Qiao; Shenglei Che; Jing Yu (Chemical Engineering Journal, 2024)

Design of a portable bioassay system based on highly efficent nanozyme and Au-DNA nanocluster: Toward current/colorimetric dual-signal detection of sugarcane smut - Danyao Tang; Zeping Wang; Rongshuai Che; Jie Liao; Meixin Yan; Xiaoqiu Zhang; Jun Yan; Ke-Jing Huang; Xuecai Tan; Yu Ya (Chemical Engineering Journal, 2024)

Riboflavin-induced microbial succession for enhanced tellurite reduction in wastewater treatment - Jiawei Jing; Bin Yu; Tingting Wang; Xinyu Guo; Pengfei Huang; Jiayue Che; Chuan Li; Yuanyuan Qu (Journal of Environmental Chemical Engineering, 2024)

Biochar decreases cadmium uptake in indica and japonica rice (Oryza sativa L.): Roles of soil properties, iron plaque, cadmium transporter genes and rhizobacteria - Meiling Xu; Meiling Ren; Yu Yao; Qi Liu; Jing Che; Xiaozhi Wang; Qiao Xu (Journal of Hazardous Materials, 2024)

Unraveling novel umami peptides from yeast extract (Saccharomyces cerevisiae) using peptidomics and molecular interaction modeling - Chunyu Gao; Rilei Yu; Xiaomei Zhang; Xue Song; Lizhi Che; Yuying Tang; Jinyue Yang; Jing Hu; Jian Xiong; Xue Zhao; Hongwei Zhang (Food Chemistry, 2024)

Micro-helical Ni3Fe chain encapsulated in ultralight MXene/C aerogel to realize multi-functionality: Radar stealth, thermal insulation, fire resistance, and mechanical properties - Sen Lin; Jing Lin; Zhiqiang Xiong; Xue He; Xin Li; Chongbo Liu; Chengying Wang; Xiaojun Zeng; Xuliang Nie; Renchao Che (Chemical Engineering Journal, 2024)

Hierarchical PVDF/ZnO/Ag/ZIF-8 nanofiber membrane used in trace-level Raman detection of H2S - Xinyu Zhang; Xin Cai; Naiqiang Yin; Yahui Che; Yang Jiao; Chao Zhang; Jing Yu; Chundong Liu (Journal of Hazardous Materials, 2024)

Effect of storage on microbioa and enzyme proteomic profile of low-temperature Daqu - Feng Liang; Zhiming Zhong; Muyan Ma; Jing Hao; Ping Ma; Jing Wu; Heqiang Huang; Fuhong Che; Qun Wu; Yan Xu (Food Bioscience, 2024)

Vertical distributions of lipid biomarkers in spring and summer in coastal regions of the East China Sea - Jiawei Gao; Shulan Xu; Rong Bi; Yaoyao Wang; Yang Ding; Hong Che; Jing Zhang; Peng Yao; Jie Shi; Meixun Zhao (Frontiers in Marine Science, 2024)
Lipid biomarkers are amongst the most widely used proxies in studies of the structure and functioning of marine food webs. However, vertical distributions of lipid biomarkers and their controlling mechanisms remain unclear, especially in highly dynamic coastal ecosystems. Here we tested vertical profiles of key lipid biomarkers (sterols and fatty acids) in suspended particles and their correlations with water masses in spring of 2017 and summer of 2018 in the Zhejiang coasts of the East China Sea. The Changjiang Diluted Water, the Taiwan Strait Water and the Kuroshio Subsurface Water showed strong contributions in the surface layer in spring, the surface layer in summer, and the deep layer in both seasons, respectively. Accordingly, lipid biomarker composition also varied between different water layers. Overall, lipid biomarker concentrations in the surface layer were around 2 ~ 7 times higher than those in the deep layer, indicating high phytoplankton biomass in the surface layer. The ratio of docosahexaenoic acid to eicosapentaenoic acid was also higher in the surface layer, especially in the south of our study region, suggesting high nutritional quality of particulate organic matters in the surface layer. Significant correlations between the depth profiles of lipid biomarkers and water masses suggested the control of water masses on lipid biomarker production. The distribution patterns of lipid biomarkers in our study are consistent with previous findings on zooplankton grazing and fish larvae, highlighting the significance of lipid biomarkers as trophic markers to study food web structure and functioning in highly dynamic coasts.

Enhanced extraction of heavy metals from gypsum-based hazardous waste by nanoscale sulfuric acid film at ambient conditions - Wenjing Li; Chunli Wang; Guiquan Che; Min Su; Zhihao Zhang; Weizhen Liu; Zhang Lin; Jing Zhang (Journal of Hazardous Materials, 2024)

Multifunctional Spirulina-hybrid helical microswimmers: Imaging and photothermal efficacy enabled by intracellular gold deposition - Ziqiao Li; Yanan Che; Ming Chen; Jing Hu; Pan He; Xiang Sun; Xiaozhen Wu; Youliang Yao; Huili Zheng; Gang Liu; Xiaohui Yan (Chemical Engineering Journal, 2024)

QTL mapping for agronomic traits in Agropyron Gaertn. CP population at the flowering stage - Yonghe Che; Jing Yang; Yutong He; Nan Song; Yanping Yang; Lai Wei; Xinming Yang; Yannong Zhang; Jinpeng Zhang; Haiming Han; Xiuquan Li; Shenghui Zhou; et al. (Euphytica, 2024)

Adsorption and enrichment of low-concentration heavy metal complexes by retractable claws made of polyelectrolyte brushes - Guiquan Che; Zhihao Zhang; Wenjing Li; Min Su; Chunli Wang; Zhengping Hao; Jing Zhang (Chemical Engineering Journal, 2024)

A novel iron sulfide phase with remarkable hydroxyl radical generation capability for contaminants degradation - Chunli Wang; Wenjing Li; Zhihao Zhang; Dashi Lei; Guiquan Che; Chunli Gou; Jing Zhang; Zhengping Hao (Water Research, 2024)

N atoms regulate heterogeneous crystal phase engineering of mesoporous magnetic FexN nanofibers to promote electromagnetic wave dissipation of magnetic composite aerogel absorbers - Wanjia Li; Wangchang Li; Zengbao Ma; Yue Kang; Ting Zou; Yu Lei; Yao Ying; Wenbo Xiang; Jing Yu; Jingwu Zheng; Liang Qiao; Juan Li; et al. (Chemical Engineering Journal, 2024)

Efficient composite chlorinated ethenes removal using gallic acid to enhance Fe/Ni nanoparticles activated persulfate - Mingda Che; Hongjian Su; Huimin Si; Bin Guo; Renliang Huang; Jing Zhao; Rongxin Su (Environmental Science and Pollution Research, 2024)

Analysis of the spatiotemporal changes in global land cover from 2001 to 2020 - Qiaoqiao Jing; Jianjun He; Yarong Li; Xianyu Yang; Yue Peng; Hong Wang; Fei Yu; Jie Wu; Sunling Gong; Huizheng Che; Xiaoye Zhang (Science of The Total Environment, 2024)

Cracking and erosion behaviors of sand–clay mixtures stabilized with microbial biopolymer and palm fiber - Jin Liu; Zi Wang; Guochang Hu; Jian Xue; Fan Bu; Miao Jing; Zezhuo Song; Wenyue Che (Science of The Total Environment, 2023)

Impacts of climate change on herpetofauna diversity in the Qinghai‐Tibetan Plateau - Alex Plimo Karuno; Xue Mi; Youhua Chen; Da‐Hu Zou; Wei Gao; Bao‐Lin Zhang; Wei Xu; Jie‐Qiong Jin; Wen‐Jing Shen; Song Huang; Wei‐Wei Zhou; Jing Che (Conservation Biology, 2023)
Although numerous studies on the impacts of climate change on biodiversity have been published, only a handful are focused on the intraspecific level or consider population‐level models (separate models per population). We endeavored to fill this knowledge gap relative to the Qinghai‐Tibetan plateau (QTP) by combining species distribution modeling (SDMs) with population genetics (i.e., population‐level models) and phylogenetic methods (i.e., phylogenetic tree reconstruction and phylogenetic diversity analyses). We applied our models to 11 endemic and widely distributed herpetofauna species inhabiting high elevations in the QTP. We aimed to determine the influence of environmental heterogeneity on species’ responses to climate change, the magnitude of climate‐change impacts on intraspecific diversity, and the relationship between species range loss and intraspecific diversity losses under 2 shared socioeconomic pathways (SSP245 and SSP585) and 3 future periods (2050s, 2070s, and 2090s). The effects of global climatic change were more pronounced at the intraspecific level (22% of haplotypes lost and 36% of populations lost) than the morphospecies level in the SSP585 climate change scenario. Maintenance of genetic diversity was in general determined by a combination of factors including range changes, species genetic structure, and the part of the range predicted to be lost. This is owing to the fact that the loss and survival of populations were observed in species irrespective of the predicted range changes (contraction or expansion). In the southeast (mountainous regions), climate change had less of an effect on range size (>100% in 3 species) than in central and northern QTP plateau regions (range size

Rebuilding high-quality near-surface ozone data based on the combination of WRF-Chem model with a machine learning method to better estimate its impact on crop yields in the Beijing-Tianjin-Hebei region from 2014 to 2019 - Tian Han; Xiaomin Hu; Jing Zhang; Wenhao Xue; Yunfei Che; Xiaoqing Deng; Lihua Zhou (Environmental Pollution, 2023)

Performance and mechanism of a novel biopolymer binder for clayey soil stabilization: Mechanical properties and microstructure characteristics - Jin Liu; Wenyue Che; Xiaowei Lan; Mengyuan Hu; Mengyao Qi; Zezhuo Song; Mengya Sun; Miao Jing; Wei Qian; Changqing Qi (Transportation Geotechnics, 2023)

Endoplasmic reticulum stress in diabetic kidney disease: adaptation and apoptosis after three UPR pathways - Ruijing Zhang; Che Bian; Jing Gao; Huiwen Ren (Apoptosis, 2023)

Simultaneous profiling of dust aerosol mass concentration and optical properties with polarized high-spectral-resolution lidar - Da Xiao; Nanchao Wang; Sijie Chen; Lingyun Wu; Detlef Müller; Igor Veselovskii; Chengcai Li; Eduardo Landulfo; Venkataraman Sivakumar; Jing Li; Huizheng Che; Jing Fang; et al. (Science of The Total Environment, 2023)

Aflatoxin B1 exposure triggers hepatic lipotoxicity via p53 and perilipin 2 interaction-mediated mitochondria-lipid droplet contacts: An in vitro and in vivo assessment - Lin Che; Jing Huang; Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Ze-Bang Du; Jia-Shen Wu; Zhong-Ning Lin; Yu-Chun Lin (Journal of Hazardous Materials, 2023)

Design of novel double-layer coated ammonium polyphosphate and its application in flame retardant thermoplastic polyurethanes - Mei Wan; Congling Shi; Xiaodong Qian; Yueping Qin; Jingyun Jing; Honglei Che; Fei Ren; Jian Li; Bin Yu; Keqing Zhou (Chemical Engineering Journal, 2023)

Molecular mechanisms of plant adaptation to acid soils: A review - Jing CHE; Xue Qiang ZHAO; Ren Fang SHEN (Pedosphere, 2023)

Numerical study of multi-jet structure impact on flue gas desulfurization process in 3D spouted beds - Xinxin Che; Feng Wu; Wenzheng Jing; Xiaoxun Ma (Chemical Engineering Journal, 2023)

Assessment of permafrost disturbances caused by two parallel buried warm-oil pipelines: A case study at a high-latitude wetland site in Northeast China - Fei Wang; Guoyu Li; Wei Ma; Dun Chen; Gang Wu; Yapeng Cao; Yanhu Mu; Yuncheng Mao; Jun Zhang; Kai Gao; Xinbin Wang; Hongyuan Jing; et al. (Cold Regions Science and Technology, 2023)

Enhanced desalination and water transport performance of polyelectrolyte-modified ‘holey’ graphene oxide film - Feng Liu; Qingwen Long; Guiquan Che; Zhihao Zhang; Mick Cooper; Jing Zhang; Gang Pan; Wentao Jiao (Journal of Cleaner Production, 2023)

Effects of shining pondweed (Potamogeton lucens) on bacterial communities in water and rhizosphere sediments in Nansi Lake, China - Nianxin Zhang; Mengmeng Wu; Yuying Che; Yong Kong; Fengyue Shu; Qingfeng Wang; Weilai Sha; Zhijin Gong; Jing Zhou (Environmental Science and Pollution Research, 2022)

Dual Drug Loaded pH-sensitive Micelles for Efficient Bacterial Infection Treatment - Yingxian Chen; Qian Zhao; Junhua Han; Xinmiao Lan; Jing Che; Meiwan Chen; Xing-Jie Liang; Xiaowei Ma (Pharmaceutical Research, 2022)

Myricitrin exerts protective effect on retina in diabetic retinopathy via modulating oxidative stress expression of VEGF and apoptosis in experimental rats: a docking confirmation study - Jing Jiang; Xin Che; Yiwen Qian; Shiheng Lu; Zhiliang Wang (Molecular & Cellular Toxicology, 2022)

Downregulated Calcium-Binding Protein S100A16 and HSP27 in Placenta-Derived Multipotent Cells Induce Functional Astrocyte Differentiation - Yu-Che Cheng; Chi-Jung Huang; Wei-Chi Ku; Shu-Lin Guo; Lu-Tai Tien; Yih-Jing Lee; Chih-Cheng Chien (Stem Cell Reviews and Reports, 2022)
Little is known about genes that induce stem cells differentiation into astrocytes. We previously described that heat shock protein 27 (HSP27) downregulation is directly related to neural differentiation under chemical induction in placenta-derived multipotent stem cells (PDMCs). Using this neural differentiation cell model, we cross-compared transcriptomic and proteomic data and selected 26 candidate genes with the same expression trends in both omics analyses. Those genes were further compared with a transcriptomic database derived from Alzheimer’s disease (AD). Eighteen out of 26 candidates showed opposite expression trends between our data and the AD database. The mRNA and protein expression levels of those candidates showed downregulation of HSP27, S100 calcium-binding protein A16 (S100A16) and two other genes in our neural differentiation cell model. Silencing these four genes with various combinations showed that co-silencing HSP27 and S100A16 has stronger effects than other combinations for astrocyte differentiation. The induced astrocyte showed typical astrocytic star-shape and developed with ramified, stringy and filamentous processes as well as differentiated endfoot structures. Also, some of them connected with each other and formed continuous network. Immunofluorescence quantification of various neural markers indicated that HSP27 and S100A16 downregulation mainly drive PDMCs differentiation into astrocytes. Immunofluorescence and confocal microscopic images showed the classical star-like shape morphology and co-expression of crucial astrocyte markers in induced astrocytes, while electrophysiology and Ca 2+ influx examination further confirmed their functional characteristics. In conclusion, co-silencing of S100A16 and HSP27 without chemical induction leads to PDMCs differentiation into functional astrocytes. Graphical abstract

The Flavor and Antioxidant Activity Change Pattern of Shrimp Head Paste During Fermentation - Jing Yu; Kuan Lu; Jinyuan Sun; Wancui Xie; Lin Song; Hongxia Che (Journal of Ocean University of China, 2022)

Characterization of municipal solid waste incineration and flue gas emission under anoxic environment in Tibet Plateau - Zeng Dan; Wenwu Zhou; Peng Zhou; Yuechi Che; Zhiyong Han; A Qiong; Bu Duo; Xuebin Lv; Qiongda Zhuoma; Jing Wang; Wang Yang; Guanyi Chen (Environmental Science and Pollution Research, 2022)

Development of a region-partitioning method for debris flow susceptibility mapping - Shuang-shuang Qiao; Sheng-wu Qin; Jing-bo Sun; Wen-chao Che; Jing-yu Yao; Gang Su; Yang Chen; Uzodigwe Emmanuel Nnanwuba (Journal of Mountain Science, 2021)

Surface warming patterns dominate the uncertainty in global water vapor plus lapse rate feedback - Jingchun Zhang; Jian Ma; Jing Che; Zhenqiang Zhou; Guoping Gao (Acta Oceanologica Sinica, 2020)

Interaction Between Planetary Boundary Layer and PM2.5 Pollution in Megacities in China: a Review - Yucong Miao; Jing Li; Shiguang Miao; Huizheng Che; Yaqiang Wang; Xiaoye Zhang; Rong Zhu; Shuhua Liu (Current Pollution Reports, 2019)
Purpose of Review During the past decades, the number and size of megacities have been growing dramatically in China. Most of Chinese megacities are suffering from heavy PM 2.5 pollution. In the pollution formation, the planetary boundary layer (PBL) plays an important role. This review is aimed at presenting the current state of understanding of the PBL-PM 2.5 interaction in megacities, as well as to identify the main gaps in current knowledge and further research needs. Recent Findings The PBL is critical to the formation of urban PM 2.5 pollution at multiple temporal scales, ranging from diurnal change to seasonal variation. For the essential PBL structure/process in pollution, the coastal megacities have different concerns from the mountainous or land-locked megacities. In the coastal cities, the recirculation induced by sea-land breeze can accumulate pollutants, whereas in the valley/basin, the blocking effects of terrains can lead to stagnant conditions and thermal inversion. Within a megacity, although the urbanization-induced land use change can cause thermodynamic perturbations and facilitate the development of PBL, the increases in emissions outweigh this impact, resulting in a net increase of aerosol concentration. Moreover, the aerosol radiative effects can modify the PBL by heating the upper layers and reducing the surface heat flux, suppressing the PBL and exacerbating the pollution. Summary This review presented the PBL-PM 2.5 interaction in 13 Chinese megacities with various geographic conditions and elucidated the critical influencing processes. To further understand the complicated interactions, long-term observations of meteorology and aerosol properties with multi-layers in the PBL need to be implemented.

α -Pyrone derivatives with cyto-protective activity from two Takla Makan desert soil derived actinomycete Nocardiopsis strains recovered in seawater based medium - Tingting Zhao; Yimin Chang; Tianjiao Zhu; Jing Li; Qianqun Gu; Dehai Li; Qian Che; Guojian Zhang (Natural Product Research, 2019)

Interferon-γ regulates cell malignant growth via the c-Abl/HDAC2 signaling pathway in mammary epithelial cells - Wen-bo Ren; Xiao-jing Xia; Jing Huang; Wen-fei Guo; Yan-yi Che; Ting-hao Huang; Lian-cheng Lei (Journal of Zhejiang University-SCIENCE B, 2019)

A corn straw-based diet increases release of inflammatory cytokines in peripheral blood mononuclear cells of dairy cows - Yan-yi Che; Xiao-jing Xia; Bo-ping He; Yuan-yuan Gao; Wen-bo Ren; Hong-tao Liu; Jian-fang Liu; Ting-hao Huang; Wen-yu Han; Lian-cheng Lei (Journal of Zhejiang University-SCIENCE B, 2018)

The Contribution of Opal-Associated Phosphorus to Bioavailable Phosphorus in Surface and Core Sediments in the East China Sea - Huanxin Li; Huijun He; Shifeng Yang; Yanli Liu; Hong Che; Mujian Li; Jing Zhang (Journal of Ocean University of China, 2018)

Silicon accumulated in the shoots results in down-regulation of phosphorus transporter gene expression and decrease of phosphorus uptake in rice - An Yong Hu; Jing Che; Ji Feng Shao; Kengo Yokosho; Xue Qiang Zhao; Ren Fang Shen; Jian Feng Ma (Plant and Soil, 2018)

Optical and radiative properties of aerosols during a severe haze episode over the North China Plain in December 2016 - Yu Zheng; Huizheng Che; Leiku Yang; Jing Chen; Yaqiang Wang; Xiangao Xia; Hujia Zhao; Hong Wang; Deying Wang; Ke Gui; Linchang An; Tianze Sun; et al. (Journal of Meteorological Research, 2017)

MicroRNA-27a Promotes Inefficient Lysosomal Clearance in the Hippocampi of Rats Following Chronic Brain Hypoperfusion - Hui Che; Yan Yan; Xiao-Hui Kang; Fei Guo; Mei-Ling Yan; Huai-Lei Liu; Xu Hou; Tong Liu; De-Kang Zong; Lin-Lin Sun; Ya-Nan Bao; Li-Hua Sun; et al. (Molecular Neurobiology, 2017)

Assessing soil microbial respiration capacity using rDNA- or rRNA-based indices: a review - Rongxiao Che; Weijin Wang; Jing Zhang; Thi Thu Nhan Nguyen; Juan Tao; Fang Wang; Yanfen Wang; Zhihong Xu; Xiaoyong Cui (Journal of Soils and Sediments, 2016)

Complex longitudinal diversification across South China and Vietnam in Stejneger's pit viper, Viridovipera stejnegeri (Schmidt, 1925) (Reptilia: Serpentes: Viperidae) - Peng Guo; Qin Liu; Fei Zhu; Guang H. Zhong; Xin Chen; Edward A. Myers; Jing Che; Liang Zhang; Thomas Ziegler; Truong Q. Nguyen; Frank T. Burbrink (Molecular Ecology, 2016)
Viridovipera stejnegeri is one of the most common pit vipers in Asia, with a wide distribution in southern China and Vietnam. We investigated historical demography and explored how the environment and climatic factors have shaped genetic diversity and the evolutionary history of this venomous snake. A total of 171 samples from 47 localities were sequenced and analysed for two mitochondrial gene fragments and three nuclear genes. Gene trees reveal the existence of two well‐supported clades (Southwest China and Southeast China) with seven distinct and strongly supported, geographically structured subclades within V. stejnegeri . Estimation of divergence time and ancestral area suggests that V. stejnegeri originated at ~6.0 Ma in the late Miocene on the Yunnan–Guizhou Plateau. The estimated date of origin and divergence of the island populations of Taiwan and Hainan closely matches the geological origin of the both islands. The mt DNA gene tree reveals the presence of west–east diversification in V. stejnegeri populations. Complex orogenesis and heterogeneous habitats, as well as climate‐mediated habitat differentiation including glacial cycles, all have influenced population structure and the distribution of this taxon. The validity of V. stejnegeri chenbihuii is questionable, and this subspecies most probably represents an invalid taxon.

Molecular phylogeography of white‐lipped tree viper ( Trimeresurus ; Viperidae) - Fei Zhu; Qin Liu; Jing Che; Liang Zhang; Xin Chen; Fang Yan; Robert Murphy; Cong Guo; Peng Guo (Zoologica Scripta, 2016)
The white‐lipped tree viper ( Trimeresurus albolabris ) is one of the most common venomous snakes with medicine importance in South East Asia. To explore the genetic diversity, population structure and evolutionary history of Trimeresurus albolabris, we collected 98 samples from 27 localities covering its entire distribution. Two mitochondrial gene fragments (cyt‐b and ND‐4) and two nuclear genes (RAG‐1 and NT‐3) were sequenced and analysed. Bayesian inference and maximum‐likelihood methods were employed to reconstruct the phylogenetic relationships among populations based on the two mitochondrial fragments, and the median‐joining networks were depicted using nuclear genes. Divergence date and ancestral area were estimated, and the population demographic history was inferred. Both phylogenetic analyses consistently uncovered that Trimeresurus albolabris was monophyletics, with five geographically structured lineages. Divergence date and ancestral area estimation indicated that T. albolabris originated in northern Thailand and eastern Myanmar at c . 7.15 Ma. Population dynamics analyses showed the southern China lineage has experienced population expansion and contraction, but the others have not. Both the interglacial expansion and the highly heterogeneous habitats resulting from the uplift of the Plateau played a joint role in shaping the present distribution and population structure. The evolutionary history of T. albolabris can be explained by a pattern of two direction dispersal: first from North to South, and then from West to East.

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Effect of in planta phosphorus on aluminum-induced inhibition of root elongation in wheat - Ji Feng Shao; Jing Che; Rong Fu Chen; Jian Feng Ma; Ren Fang Shen (Plant and Soil, 2015)

Discussion on evaluating the vulnerability of storm surge hazard bearing bodies in the coastal areas of Wenzhou - Yuexia Zhang; Jing Guo; Zhumei Che (Frontiers of Earth Science, 2015)

Aspirin and nonsteroidal anti-inflammatory drugs after but not before diagnosis are associated with improved breast cancer survival: a meta-analysis - Xuan-zhang Huang; Peng Gao; Jing-xu Sun; Yong-xi Song; Cheng-che Tsai; Jing Liu; Xiao-wan Chen; Ping Chen; Hui-mian Xu; Zhen-ning Wang (Cancer Causes & Control, 2015)

Synthesis and antibacterial evaluation of furan derivatives bearing a rhodanine moiety - Jian Che; Chang-Ji Zheng; Ming-Xia Song; Ya-Jing Bi; Yi Liu; Yin-Jing Li; Yan Wu; Liang-Peng Sun; Hu-Ri Piao (Medicinal Chemistry Research, 2014)

Ectopic Expression of Sweet Potato Cysteine Protease SPCP3 Alters Phenotypic Traits and Enhances Drought Stress Sensitivity in Transgenic Arabidopsis Plants - Hsien-Jung Chen; Yi-Jing Tsai; Che-Yu Shen; Ting-No Tsai; Guan-Jhong Huang; Yaw-Huei Lin (Journal of Plant Growth Regulation, 2013)

Geological events play a larger role than P leistocene climatic fluctuations in driving the genetic structure of Q uasipaa boulengeri ( A nura: D icroglossidae) - Fang Yan; Weiwei Zhou; Haitao Zhao; Zhiyong Yuan; Yunyu Wang; Ke Jiang; Jieqiong Jin; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Paleoclimatic and paleogeological events have been identified as being the two main drivers of genetic structuring in extant organisms. We used a montane stream‐dwelling frog, Q uasipaa boulengeri , to explore the relative roles played by these drivers on species in southern C hina, a region needing thorough studies. We detected four major matrilines, and no broadly distributed haplotypes occurred. The complex orogenesis of south‐western China drove matrilineal divergence in Q . boulengeri into highly structured geographical units. These matrilines subsequently persisted in situ with stable populations rather than undergoing expansions during glacial cycling. The unification of the upper and middle Y angtze R iver in the Three Gorges mountain region mediated downstream colonization of this frog. Analyses identified geological events as playing a larger role than climatic fluctuations in driving the population history of Q . boulengeri . Nuclear allele analyses indicated gene flow; this maintained genetic cohesion of the species. S outh‐eastern S ichuan B asin was identified as the area of secondary contact for several matrilines, and this area deserves further study and special protection.

River islands, refugia and genetic structuring in the endemic brown frog R ana kukunoris ( A nura, R anidae) of the Q inghai‐ T ibetan P lateau - Weiwei Zhou; Fang Yan; Jinzhong Fu; Shifang Wu; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Frequently, P leistocene climatic cycling has been found to be the diver of genetic structuring in populations, even in areas that did not have continental ice sheets, such as on the Q inghai‐ T ibetan P lateau ( QTP ). Typically, species distributed on the plateau have been hypothesized to re‐treat to south‐eastern refugia, especially during the L ast G lacial M aximum ( LGM ). We evaluated sequence variation in the mitochondrial DNA gene Cytb and the nuclear DNA gene RAG ‐1 in R ana kukunoris , a species endemic to the QTP . Two major lineages, N and S, were identified, and lineage N was further subdivided into N 1 and N 2. The geographical distribution and genealogical divergences supported the hypothesis of multiple refugia. However, major lineages and sublineages diverged prior to the LGM . Demographical expansion was detected only in lineage S and sublineage N 2. Sublineage N 1 might have survived several glacial cycles in situ and did not expand after the LGM because of the absence of suitable habitat; it survived in river islands. Genetic analysis and environment modelling suggested that the north‐eastern edge of QTP contained a major refugium for R . kukunoris . From here, lineage S dispersed southwards after the LGM . Two microrefugia in northern Q ilian M ountains greatly contributed to current level of intraspecific genetic diversity. These results were found to have important implications for the habitat conservation in N orthwest C hina.

Speciation in the Rana chensinensis species complex and its relationship to the uplift of the Qinghai–Tibetan Plateau - WEI‐WEI ZHOU; YANG WEN; JINZHONG FU; YONG‐BIAO XU; JIE‐QIONG JIN; LI DING; MI‐SOOK MIN; JING CHE; YA‐PING ZHANG (Molecular Ecology, 2012)
Speciation remains a fundamental issue in biology. Herein, we report an investigation into speciation in the Rana chensinensis species complex using DNA sequence data from one mitochondrial and five nuclear genes. A phylogenetic analysis of the data revealed four major clades in the complex, and each of them was found to likely represent a species, including one cryptic species. Ecological niche models were generated from 19 climatic variables for three of the four major clades, which were represented by widespread sampling, including R. chensinensis , Rana kukunoris and the potential cryptic species. Each clade is associated with a unique ecological unit, and this indicates that ecological divergence probably drove speciation. Ecological divergence is likely related to the late Cenozoic orogenesis of the Qinghai–Tibetan Plateau. In addition, gene flow between species was detected but only in peripheral portions of the ranges of the four major clades, thus likely had little influence on the speciation processes. Discordances between mitochondrial and nuclear genes were also found; the nominal species, R. chensinensis , contains multiple maternal clades, suggesting potential mitochondrial introgression between R. chensinensis and R. kukunoris .

Effect of 1-methylcyclopropene on postharvest physiological changes of ‘Zaohong’ plum - Juan Kan; Jing Che; Hai Yan Xie; Chang Hai Jin (Acta Physiologiae Plantarum, 2011)

Eukaryotic expression and purification of anti-epilepsy peptide of Buthus martensii Karsch and its protein interactions - Zongren Wang; Wen Wang; Zhongjun Shao; Bifeng Gao; Junchang Li; Jing Ma; Jinghua Li; Honglei Che; Wei Zhang (Molecular and Cellular Biochemistry, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)